High Prevalence of Self-Reported Photophobia in Adult ADHD - Kooij, J. J. Sandra; Bijlenga, Denise (Frontiers in Neurology, 2014)
Many adult outpatients with ADHD report an oversensitivity to light. We explored the link between ADHD and photophobia in an online survey (N=494). Self-reported photophobia was prevalent in 69% of respondents with, and in 28% of respondents without, ADHD (symptoms). The ADHD (symptoms) group wore sunglasses longer during daytime in all seasons. Photophobia may be related to the functioning of the eyes, which mediate dopamine and melatonin production systems in the eye. In the brain, dopamine and melatonin are involved in both ADHD and circadian rhythm disturbances. Possibly, the regulation of the dopamine and melatonin systems in the eyes and in the brain are related. Despite the study’s limitations, the results are encouraging for further study on the pathophysiology of ADHD, eye functioning, and circadian rhythm disturbances.